Determinan Faktor Risiko Kejadian Preeklamsia Pada Ibu Hamil: Studi Literatur - Suparji, Suparji; Surtinah, Nani; Latif, Abdul (Madu : Jurnal Kesehatan, 2024)
This article is the result of a systematic review which aims to identify determinants of risk factors for preeclampsia in pregnant women. This research uses the Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) method with the Google Scholar database. The results of this review involved 20 articles which were excluded to become 12 relevant articles, and finally 6 articles were selected that were appropriate to the research topic. The selected articles discuss the relationship between gravida risk factors and the incidence of preeclampsia, as well as risk factors for the incidence of preeclampsia in pregnant women. The results of the review show that gravida factors, maternal age, parity, pregnancy spacing, and history of hypertension can influence the incidence of preeclampsia in pregnant women. The conclusion of this article is that there are many risk factors that can cause preeclampsia in pregnant, giving birth and postpartum women. Although there are more dominant risk factors, preeclampsia can be treated and prevented through optimal antenatal monitoring and early detection. It is recommended that health service facilities and health workers can optimize antenatal supervision, early detection and good treatment to prevent severe preeclampsia and reduce maternal mortality. Apart from that, the community, especially pregnant, giving birth and postpartum women, is expected to play a more active role in preventing preeclampsia and pay attention to the causes and ways to avoid preeclampsia and its complications.